2017
DOI: 10.2527/jas2016.1032
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem protein degradation is a key contributor to fresh pork loin tenderness

Abstract: The objective of this study was to determine factors that influence tenderness independent of variation in pH, color, or marbling. To achieve the objective, 2 sample groups were chosen from a population of 159 pork loins aged 11 to 16 d. Predetermined ranges (ultimate pH, 5.54 to 5.86; marbling score, 1.0 to 3.0; percent total lipid, 1.61 to 3.37%) were defined for inclusion of individual loins in the study. The pork loins with the greatest (n = 12) and least (n = 12) Instron star probe values were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
(65 reference statements)
1
18
0
1
Order By: Relevance
“…Moreover, the disappearance of the structural proteins could be indicating more proteolysis. These differences in myofibrillar protein degradation might lead to a variation in tenderness as previously reported in pork (Carlson et al ., ). However, molecular differences sometimes produce no effect at macroscopic level.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the disappearance of the structural proteins could be indicating more proteolysis. These differences in myofibrillar protein degradation might lead to a variation in tenderness as previously reported in pork (Carlson et al ., ). However, molecular differences sometimes produce no effect at macroscopic level.…”
Section: Resultsmentioning
confidence: 97%
“…Rate of troponin -T degradation has been documented to be inversely related to WBSF in pork (Szalata et al, 2005). Carlson et al (2017b) reported 26 % less abundant intact troponin-T in low star probe samples than high star probe samples (P < 0.01) in aged pork chop samples. Abundance of the 30-kDa degradation band and 27 -30 kDa degradation product of troponin-T in low star probe samples was more than double the abundance of troponin-T degradation products in high star probe samples (P < 0.01).…”
Section: Troponinmentioning
confidence: 89%
“…These fibers were also larger in cross sectional area when compared to the fibers in distal locations. It has been well documented that postmortem degradation of troponin-T (Huff- Carlson et al, 2017b) and desmin Melody et al, 2004;Rowe et al, 2004a;Carlson et al, 2017a;Carlson et al, 2017b) is linked to meat tenderness.…”
Section: Postmortem Protein Degradationmentioning
confidence: 99%
“…Up till now, many efforts have been made to identify possible candidate genes effecting fat‐related traits. FASN (fatty acid synthase), LPL (lipoprotein lipase), FABP3 (fatty acid‐binding protein 3, also known as heart‐type FABP, H‐FABP) , and FABP4 (fatty acid‐binding protein 4, also known as adipocyte FABP, A‐FABP ) have been regarded to be associated with intramuscular fat (IMF) deposition (Gao & Zhao, ; Yamada, ), while members of the calpain (CAPN) family, CAPN1 , CAPN2 , and CAST (calpastatin), are considered to be closely related to post‐mortem meat tenderness (Carlson et al., ; Lian, Wang, & Liu, ). Also, many documents showed the associations between polymorphisms on these genes and meat traits in meat‐producing animals (Gao et al., ; Liang et al., ; Oh et al., ; Pinto et al., ; Rempel, Casas, Shackelford, & Wheeler, ; Ye, Chen, Zhao, Zheng, & Wen, ).…”
Section: Introductionmentioning
confidence: 99%